Effects of nanoscale ridge/groovepattern arrayed surface on in vitro differentiation of multi-potent pulp cells derived from human supernumerary teeth - Kim, Daehwan; Jo, Hwansung; Lee, Jingu; Kim, Keesung; Roh, Sangho (International journal of oral biology, 2013)
Human dental pulp stem cells (DPSCs) are multi-potent mesenchymal stem cells that have several differentiation potentials. An understanding of thetissues that differentiate from these cells can provide insights for future regenerative therapeutics and tissue engineering strategies. The mesiodens is the most frequent form of supernumerary tooth from which DPSCs can differentiate into several lineages similar to cells from normal deciduous teeth. Recently, it has been shown that nanoscale structures can affect stem cell differentiation. In our presentstudy, we investigated the effects of a 250-nm nanoscale ridge/groove pattern array on the osteogenic and adipogenic differentiation of dental pulp cells from mesiodenscontaining human DPSCs. To this end, the expression of lineage specific markers after differentiation induction was analyzed by lineage specific staining and RT-PCR. The nanoscale pattern arrayed surface showed apositive effect on the adipogenic differentiation of DPSCs. There was no difference between nanoscale pattern arrayed surface and conventional surface groups onosteogenic differentiation. In conclusion, the nanoscale ridge/groove pattern arrayed surface can be used to enhance the adipogenic differentiation of DPSCs derived from mesiodens. This finding provides an improved understanding of the effects of topography on cell differentiation as well as the potential use of supernumerary tooth in regenerative dental medicine.